Rancangan Alat Absensi Berbasis Internet of Things dan Notifikasi Smartphone Menggunakan App Inventor - Warman, Aziz; Jufrizel, Jufrizel; Ullah, Aulia; Zarory, Hilman (Universitas Budi Darma, 2024)
Technological developments have become a major focus when it comes to improving everyday productivity and innovation. Intelligent tools are created to facilitate and assist human work in life. Smart attendance machines are designed to replace the role of manual paper attendance and switch to an automated system. The problem with manual attendance is that there is potential for fraud in attendance and attendance data is vulnerable to damage and loss of data because it only uses paper media for storage and the use of manual attendance also has disadvantages related to attendance data that can be known by student guardians every day. This paper discusses the design of an attendance system using a Radio Frequency Identification (RFID) card as an identity used for the attendance process. The use of Liquid Crystal Display (LCD) to display information from card readings. ESP8266 microcontroller is used to run commands according to the program and access to Wifi that can connect to the internet. To store attendance data using application software that can be accessed by the admin. To monitor attendance, App Inventor is used which can be connected to a smartphone. The results of testing the tool show that the attendance machine can operate in accordance with the design and provide satisfactory results, the tool works by attaching the identity card to the card reader and the data will appear on the LCD in the form of card ID and attendance information, the time it takes to read the card until it appears on the LCD is 2-3 seconds. Attendance data in the form of names, hours in, hours out and attendance information is successfully sent to the website application via an internet connection with the average time required of 4.43 seconds. Data in the form of sample photos was successfully sent by ESPcam to the website application via an internet connection with an average delivery time of 9.36 seconds. The attendance message was successfully sent to the Smartphone using App Inventor.